PET/CT with 18F-Fluorocholine in Patients with Prostatic Cancer in Biochemical Recurrence - Lapa, Paula (2016)
Introduction: In prostate cancer, after therapy with curative intent, biochemical recurrence frequently occurs. The purpose of this study was to evaluate the impact of PET/CT with 18F-fluorocholine in restaging these patients and in their orientation, and to analyze the effect of the risk stratification, the values of PSA and the hormone suppression therapy, in the technique sensitivity. Material and Methods: Retrospective analysis of 107 patients with prostate carcinoma in biochemical recurrence who underwent PET/CT with 18F-fluorocholine in our hospital, between December 2009 and May 2014. Results: The overall sensitivity was 63.2% and 80.0% when PSA > 2 ng/mL. It was possible to identify distant disease in 28% of the patients. The sensitivity increased from 40.0%, in patients with low and intermediate risk, to 55.2% in high-risk patients. Without hormonal suppression therapy, the sensitivity was 61.8%, while in the group under this therapy, was 67.7%. Discussion: PET/CT with 18F-fluorocholine provided important information even in patients with low levels of PSA, however, with significantly increased sensitivity in patients with PSA > 2 ng/mL. Sensitivity was higher in high-risk patients compared with low and intermediate risk patients, however, without a statistically significant difference. The hormone suppression therapy does not appear to influence uptake of 18F-fluorocholine in patients resistant to castration. Conclusions: In this study, PET/CT with 18F-Fluorocholine showed good results in restaging patients with prostate cancer biochemical recurrence, distinguishing between loco regional and systemic disease, information with important consequences in defining the therapeutic strategy.